2018
DOI: 10.3389/fcvm.2018.00157
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function During Extracorporeal Membrane Oxygenation in Adult Patients: A Systematic Review

Abstract: Background: Hemorrhagic and thromboembolic complications are common during treatment with extracorporeal membrane oxygenation (ECMO), resulting in considerable morbidity and mortality. This emphasizes the clinical relevance of understanding hemostatic changes occurring during ECMO treatment. As platelets are key players in hemostasis, detailed knowledge on how ECMO treatment affects platelet function is of great importance. We therefore aimed to systematically summarize and discuss existing knowledge on platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 44 publications
(111 reference statements)
0
36
0
Order By: Relevance
“…In a systematic recent review, Balle et al reported that there are only a limited number of published studies investigating platelet functions in patients during ECMO therapy. These studies suggest a reduced potential for platelet adhesion, activation, and aggregation during ECMO [7].…”
Section: Platelet Activation Aggregation and Ecmomentioning
confidence: 75%
“…In a systematic recent review, Balle et al reported that there are only a limited number of published studies investigating platelet functions in patients during ECMO therapy. These studies suggest a reduced potential for platelet adhesion, activation, and aggregation during ECMO [7].…”
Section: Platelet Activation Aggregation and Ecmomentioning
confidence: 75%
“…It is widely acknowledged that the majority of COVID-19 patients, especially those with severe disease, are characterized by lymphocytopenia. This laboratory symptom is observed mostly in adult patients, much less often to children [45], and may predict COVID-19 severity [53]. The second important remark is that the reduced number of lymphocytes is also a common feature of diseases caused by other coronaviruses, including SARS [54] and MERS [55].…”
Section: Laboratory Disorders In Sars-cov-2 Infection Vs V-v Ecmomentioning
confidence: 99%
“…For the studies included in this systematic review, a thorough assessment of the methodological quality and risk of bias analysis was performed by two authors (NM and PB) independently. The Newcastle-Ottawa Scale (NOS) was used for case-control studies [28, 29], while the case series studies were appraised using National Heart, Lung, and Blood Institute (NHLBI) Study Quality Assessment Tools [30, 31]. NOS for case-control studies included three criteria 1) Selection (which was evaluated based on a) if the case definition was adequate, b) representativeness of the cases, c) selection of controls and d) definition of controls; 2) Comparability (evaluated based on the comparability of case and controls in terms of study design and data analysis); 3) Exposure (assessed by a) ascertainment of exposure, b) whether or not the same method of ascertainment was applied for cases and controls, and c) non-response rate).…”
Section: Methodsmentioning
confidence: 99%